Morphofunctional characteristics of leaves and fruits in Maloideae (Rosaceae): a. Microstructure of surface tissues - T. Kh. Kumachova; A. S. Voronkov; A. V. Babosha; A. S. Ryabchenko (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. The formation of cover tissues (epidermis, cork), providing a connection with the environment, in the evolution of flowering plants was one of the main consequences of the transition to life on earth. The epidermis, which emerged as a device for protecting deeper underlying tissues from drying, subsequently acquired additional functions (participation in gas exchange and transpiration, absorption and isolation of certain substances as well as protection from the penetration of pathogens) and became a multifunctional tissue consisting of several types of cells (basic, stomatal, and trichomes). Features of the fine structure of the epidermis are of interest in representatives of the subfamily Maloideae Werber (Rosaceae Juss.), which grow, inter alia in mountain agrobiocenoses with their rather harsh conditions. They extended their area of distribution to various habitats due to the development of structural adaptations that play an important role in the formation of resistance to stressors of different etiologies.Objective. Representatives of 4 genera were chosen as model objects from subfam. Maloideae for the study: Malus domestica Borkh., Pyrus communis L., Cydonia oblonga Mill., and Mespilus germanica L.Materials and methods. Mature leaves and fruits were selected from the middle part of the crown of three model trees of each species. The samples were studied by scanning electron microscopy (SEM), with a freezing attachment.Results. Leaves of Maloideae were found to be hypostomatic, while the abaxial (lower) epidermis is multifunctional: it performs a barrier function together with the cuticle. Formation of the cuticular nature can be attributed to the surface structures: peristomatic rings and ridges as well as radially extending folds, all forming a specific microrelief. The adaxial (upper) and abaxial surfaces clearly differ not only in the features of the structure, but also in the specificity of the microrelief’s arrangement. Species-specific traits were also found in the structure of the surface tissue of the pericarp. M. germanica, unlike the other species, does not have a continuous cuticular cover and wax deposits: most of a mature fruit’s surface is covered with a peeling cork layer. In the study of the surface of C. oblonga fruits, numerous rather large stomata with peristomatic rings and cuticular cushions were found similar to those in leaves.Conclusion. Surface structures of leaves and fruits in subfam. Maloideae include formations of cuticular nature, with different specificities of microrelief shaping due to the functional load of the epidermal tissue and environmental conditions. They can also be involved in building resistance to biotic stressors. The obtained data on the features of the fine structure of surface tissues are of interest for applied and theoretical studies, especially environmental and botanical, relating to taxonomic issues.